I have to solve the following differential equation:

$$(\cos^2x + y \sin 2x) \frac{dy}{dx} + y^2 =0$$

using an integrating factor. An integrating factor that is a function of just $x$ or just $y$ won't work, so we need to find an integrating factor which is a function of both $x$ and $y$.

I have followed the instructions from this other post Finding integrating factor when IF will be a function of x and y which suggests looking for a separable solution:

$$u(x,y)=e^{\int G(x) dx} e^{\int F(y) dy}$$

where $G(x)=\frac{\delta u/\delta x}{u}$ and $F(y)=\frac{\delta u/\delta y}{u}$. However, I get stuck at this point:

$$G(x)(\cos^2 x + y \sin 2x) - F(y) y^2 = 2y + 2 \sin 2x - 2y \cos 2x$$

and I can't find a solution for $G(x)$ and $F(y)$ that would work.

Any ideas? Thanks in advance!


Let's rewrite the equation in this form: \begin{equation*} \underbrace{y^2}_M \,\mathrm dx + \underbrace{(\cos^2 x + y \sin 2x)}_N \,\mathrm dy = 0. \end{equation*}

Let $u(x,y)$ be an integrating factor. Then after multiplying the above equation by $u$, the resulting equation $uM \,\mathrm dx + uN \,\mathrm dy = 0$ should be exact. Thus, we must have

\begin{align*} \dfrac{\partial (uM)}{\partial y} = \dfrac{\partial (uN)}{\partial x} \implies\\ u M_y + u_y M = u N_x + u_x N \implies\\ u(M_y - N_x) = u_x N - u_y M. \end{align*}

Since $M = y^2$ and $N = \cos^2 x + y \sin 2x$, we have $M_y = 2y$ and $N_x = - \sin 2x + 2y \cos2x$, so that $M_y - N_x = \sin 2x + 2y (1 - \cos 2x) = 2\sin x \cos x + 4y \sin^2 x = 2\sin x (\cos x + 2y \sin x)$.

Note that $N = \cos^2 + 2y \sin x \cos x = \cos x (\cos x + 2y \sin x)$.

Thus, we have \begin{align*} M_y - N_x & = 2 \sin x (\cos x + 2y \sin x)\\ N & = \cos x (\cos x + 2y \sin x). \end{align*}

Now, if it happened that $u$ were only a function of $x$, then $u_y = 0$, and our earlier condition for exactness would become \begin{equation*} u(M_y - N_x) = u_x N \implies \dfrac{u_x}{u} = \dfrac{M_y - N_x}{N}. \end{equation*}

Indeed, this would be true if the RHS turned out to be a function of $x$ alone. Observe that this is so, for $\dfrac{M_y - N_x}{N} = 2 \tan x$.

Thus, $$\dfrac{u_x}{u} = 2 \tan x \implies \log u = \int 2 \tan x \,\mathrm dx = 2 \log \sec x.$$ Therefore, $$u = \sec^2 x$$ is the integrating factor.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.